1997
DOI: 10.1006/dbio.1997.8571
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Morphogenetic Movement duringXenopusGastrulation by Injected Sulfatase: Implications for Anteroposterior and Dorsoventral Axis Formation

Abstract: In order to explore the role of morphogenetic movement in the establishment of anteroposterior and dorsoventral axes, we sought to identify novel in vivo inhibitors of gastrulation movements in Xenopus laevis. Injection of hydrolytic sulfatase into the blastocoels of gastrula stage embryos resulted in severe anteroposterior truncation, without a corresponding truncation of the dorsoventral axis. Confocal microscopy of whole embryos revealed that gastrulation movements are severely disrupted by sulfatase; in ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

1998
1998
2012
2012

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 34 publications
1
10
0
Order By: Relevance
“…At later stages of development, an increase of IDS sulfatase activity during gastrulation prompted to a possible critical role during developmental stages, when blastodermal cells start to move and give rise to the three germ layers. A preliminary observation for a key role of sulfatases in convergent movements during gastrulation has been already reported in Xenopus (Wallingford et al, 1997). Here, we have shown that ids knockdown is associated with the expansion of mesendodermal territories and this result fits with previous observations that in the mouse heparan sulfate and chondroitin sulfate are enriched in mesodermal territories during gastrulation (Garcia-Garcia and Anderson, 2003).…”
Section: Discussionsupporting
confidence: 92%
“…At later stages of development, an increase of IDS sulfatase activity during gastrulation prompted to a possible critical role during developmental stages, when blastodermal cells start to move and give rise to the three germ layers. A preliminary observation for a key role of sulfatases in convergent movements during gastrulation has been already reported in Xenopus (Wallingford et al, 1997). Here, we have shown that ids knockdown is associated with the expansion of mesendodermal territories and this result fits with previous observations that in the mouse heparan sulfate and chondroitin sulfate are enriched in mesodermal territories during gastrulation (Garcia-Garcia and Anderson, 2003).…”
Section: Discussionsupporting
confidence: 92%
“…This indicates that these anterior truncations arise from an interference with anteroposterior patterning as opposed to the anterior truncations that result from UV light‐induced perturbations during the establishment of dorsoventral polarity. A similar distinction has recently been drawn for effects on anteroposterior pattern that arise from the blastocoel injection of sulfatase (Wallingford et al ., 1997).…”
Section: Resultsmentioning
confidence: 99%
“…For example, it has been shown that in hybrids of Rana species in which convergent extension is defective, archenteron elongation can proceed (Gregg, 1957;Gregg and Klein, 1955;Moore, 1946). Likewise, hydrolytic sulfatase disrupts convergent extension potently, and whereas archenteron inflation is severely affected, archenteron elongation is only mildly reduced (Wallingford et al, 1997).…”
Section: Convergent Extension Marginal Zone Internalization and Blasmentioning
confidence: 99%